2010
DOI: 10.1111/j.1475-679x.2010.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

CEO Turnover and Retention Light: Retaining Former CEOs on the Board

Abstract: Prior CEO turnover literature characterizes the board's decision as a choice between retaining versus replacing the CEO. We focus instead on the CEO's decision rights and introduce a third option in which the incumbent CEO is removed but retained on the board for an extended period, which we call Retention Light. Firms may benefit from Retention Light because former CEOs possess unique monitoring and advising abilities, but the former CEO could also exploit available decision rights for personal benefit. A Ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 49 publications
(124 reference statements)
7
41
1
Order By: Relevance
“…In addition, some authors reported a negative result like Evans et al (2010), Maury (2006) and Garcia et al (2006). A similar negative result was revealed between CEO tenure and firm performance by studies dedicated to the developing countries (e.g.…”
Section: Ceo Tenure and Firm Performancementioning
confidence: 61%
“…In addition, some authors reported a negative result like Evans et al (2010), Maury (2006) and Garcia et al (2006). A similar negative result was revealed between CEO tenure and firm performance by studies dedicated to the developing countries (e.g.…”
Section: Ceo Tenure and Firm Performancementioning
confidence: 61%
“…The control variables we employ have been shown to be significant determinants of CEO selection in several studies including Borokhovich et al (1996), Evans, Nagarajan, and Schloetzer (2010), Fahlenbrach, Minton, and Pan (2008, Fredrickson, Hambrick, and Baumrin (1988), Guthrie and Datta (1997), Parrino (1997), Zajac and Westphal (1996), and Zhang and Rajagopalan (2003). We examine whether they also influence a firm's decision to hire a CEO from within or outside its industry.…”
Section: The Determinants Of Ceo Selectionmentioning
confidence: 99%
“…Chen and Hambrick, 2012;Evans et al, 2010;Huson, Malatesta, and Parrino, 2004). Chen and Hambrick, 2012;Evans et al, 2010;Huson, Malatesta, and Parrino, 2004).…”
Section: Human Capital and Firm Performancementioning
confidence: 99%